Em busca do fortalecimento linguístico : retrato metalexicográfico dos primeiros registros da língua Manoki - Oliveira, Alex Feitosa (2023)
In this thesis, we have as main objective to analyze the first records of the Manoki language, authored by a Jesuit missionary, Fr. José de Moura e Silva, published in 1957 and 1960. The language recorded in the works is classified as isolated and spoken by the Manoki and Mỹky peoples. Currently, these groups inhabit the Irantxe, Mỹky and Tirecatinga Indigenous Lands, located in the municipalities of Brasnorte and Sapezal, in Mato Grosso. Due to the interdisciplinary nature of this study, we deal with the documented history of contact with the surrounding society, with attention to the process of linguistic displacement intensified by the coexistence of the Manoki with the missionaries. Then, because it is a guiding thread of the construction of this research, we draw an overview about the main official Brazilian language policies related to indigenous languages. Inserted in this theme, we discuss the linguistic silencing experienced by different indigenous peoples and, finally, we point out some actions currently developed among the Manoki as policies of resistance. For the proposed analysis, we are based on the Sciences of the Lexicon, from Biderman (1998), Welker (2004), Lara (2003), Fargetti and Vanetti (2018) and Bumlai (2022). Thus, this research is framed as bibliographic and documental. From the results achieved, we unveil the sociolinguistic situation of the people at the time of the first documentation of the language and, at the same time, an ideological dispute over its description. In addition, we identified and recorded the phonetic traits raised by Fr. José de Moura e Silva, based on the restitutive method proposed by Constenla Umaña (2000). In the end, from a strategy of contrastive lemmas of Bumlai (2022), we investigate the morphological hypotheses postulated by the author. Despite the little prestige conferred to the lexicographic works of Moura (1957, 1960), we found, based on the data analyzed, the importance of these records both for the historical and sociolinguistic information, as well as for the cultural aspects and, especially, because it is the capture of a stage of the language at the time of the first contacts with the people. This thesis, therefore, seeks to give greater prominence to studies classified as unsystematic and, at the same time, to contribute to the process of linguistic-cultural reconstruction currently experienced by the Manoki.